Crack Repair by Epoxy – Injection Method vs. Gravity Feed Method - Yadollahi Mohammad (MATEC Web of Conferences, 2025)
One of the potentially effective concrete crack repair methods is filling the crack with epoxy resin (“epoxy”). There are two main repair methods using epoxy: (i) epoxy injection; and (ii) gravity feed with epoxy. In the epoxy injection method, the epoxy is injected under pressure into the cracks, while the gravity feed by epoxy method uses a thin epoxy to penetrate and fill the crack by gravity alone. Although these two methods have some similarities, their applications and objectives vary. It is crucial to assess and determine the cause(s) of the cracking and understand the objective of the repair prior to repairing any concrete crack. The primary objective of crack repair by gravity feed with epoxy is to fill and seal the cracks that are not moving – for example, shrinkage cracks and settlement cracks that have stabilised. However, the primary objective of the epoxy injection method is to restore the structural integrity and the resistance to penetration of the concrete element by aggressive liquids. This paper compares and contrasts the above two methods, and in order to enable the reader to select the most effective technique for a concrete crack repair project, explores through a case study: (i) the effectiveness of these repair methods to adequately seal cracks; (ii) the ability of these repair methods to fully penetrate the entire length of the cracks; and (iii) their fitness to create a long-term repair solution.